2013
DOI: 10.1109/ted.2013.2247042
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Permittivity of Porous Si for Use as Substrate Material in Si-Integrated RF Devices

Abstract: Dielectric permittivity of porous Si (PSi) layers formed on a low-resistivity p-type Si (0.001-0.005 .cm) is thoroughly investigated using analytical expressions within the frame of broadband transmission line characterization method in the frequency range 1-40 GHz. It is demonstrated that the value of Si resistivity is critical for the resulting PSi layer permittivity even within the above limited resistivity range. The real part of PSi dielectric permittivity changes monotonically between 1.8 and 4 by changi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 32 publications
(46 reference statements)
2
24
0
1
Order By: Relevance
“…The porous Si layer is then capped with a 500 nm SiO 2 layer in order to protect it from environmental variations. The authors also demonstrated in [16] that the structure and morphology of the PSi layer, and consequently its dielectric parameters, depend on the Si wafer resistivity, even in the above limited resistivity range used. So, six different porous Si layers were created, all starting from Si wafers of different resistivity value within the range of 1-5 mΩ.cm.…”
Section: A Porous Si Formationmentioning
confidence: 97%
See 4 more Smart Citations
“…The porous Si layer is then capped with a 500 nm SiO 2 layer in order to protect it from environmental variations. The authors also demonstrated in [16] that the structure and morphology of the PSi layer, and consequently its dielectric parameters, depend on the Si wafer resistivity, even in the above limited resistivity range used. So, six different porous Si layers were created, all starting from Si wafers of different resistivity value within the range of 1-5 mΩ.cm.…”
Section: A Porous Si Formationmentioning
confidence: 97%
“…The resulting material is uniform throughout its thickness, which exceeds 150 μm. As demonstrated by the authors in [16], this thickness is enough to provide full electromagnetic (EM) isolation [17] from the underlying Si substrate. The porous Si layer is then capped with a 500 nm SiO 2 layer in order to protect it from environmental variations.…”
Section: A Porous Si Formationmentioning
confidence: 99%
See 3 more Smart Citations